Elephants or onions? Paying for nature in Amboseli, Kenya - Bulte, E.; Boone, R.; Stringer, R.; Thornton, Philip K. (Cambridge University Press, 2008)
Traditional grazing grounds near Amboseli National Park (Kenya) are being rapidly converted to cropland – a process that closes important wildlife corridors. We use a spatially explicit simulation model that integrates ecosystem dynamics and pastoral decision-making to explore the scope for introducing a ‘payments for ecosystem services’ scheme to compensate pastoralists for spillover benefits associated with forms of land use that are compatible with wildlife conservation. Our break-even cost analysis suggests that the benefits of such a scheme likely exceed its costs for a large part of the study area, but that ‘leakage effects’ through excessive stocking rates warrant close scrutiny.